Pengaruh Orientasi Pasar terhadap Kinerja Kafe di Malang yang Dimediasi oleh Strategi Bersaing - SE, Radiyatan Mardhiyah (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research is motivated by the increasingly intense business competition rhar requires entrepreneurs to create an added value for their customers. This study aims to identity the influence of market orientation on kafe’s performance with the mediation of competitive strategy. The sample of this explanatory research is 74 respondents selected through convenience sampling. The data was analyzed using path analysis, and the hypothesis was tested using t-tes and sobel test in SPSS 25. The result shows that the market orientation has a effect on competitive strategy, market orientation has no effect on kafe’s performance, and competiitve strategy has a effect on kafe’s performance. However, competiitve startegy does not have any indirect effect on market orientation through kafe’s performance. Keywords: Market Orientation, Competiitve Strategy, Kafe’s Performance.